2016
DOI: 10.1128/jb.00583-16
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bacillus Spore Small Molecules, rRNA, Germination, and Outgrowth after Extended Sublethal Exposure to Various Temperatures: Evidence that Protein Synthesis Is Not Essential for Spore Germination

Abstract: ABSTRACTrRNAs of dormant spores of Bacillus subtilis were >95% degraded during extended incubation at 50°C, as reported previously (E. Segev, Y. Smith, and S. Ben-Yehuda, Cell 148:139 -114, 2012, doi:http://dx.doi.org/10.1016/j.cell.2011.11.059), and this was also true of spores of Bacillus megaterium. Incubation of spores of these two species for ϳ20 h at 75 to 80°C also resulted in the degradation of all or the great majority of the 23S and 16S rRNAs, although this rRNA degradation was slower than nonenzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
45
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 51 publications
2
45
1
Order By: Relevance
“…A recent paper published by the Setlow laboratory (Korza et al, 2016) presumably challenges our findings, claiming that protein synthesis is not required for germination. This discrepancy was highlighted by a commentary written by Boone and Driks (2016), thoroughly comparing the two papers.…”
contrasting
confidence: 58%
See 3 more Smart Citations
“…A recent paper published by the Setlow laboratory (Korza et al, 2016) presumably challenges our findings, claiming that protein synthesis is not required for germination. This discrepancy was highlighted by a commentary written by Boone and Driks (2016), thoroughly comparing the two papers.…”
contrasting
confidence: 58%
“…However, even with these methodological weaknesses, when we closely examined and quantified their data, we could clearly see an increase in rRNA levels at time points corresponding to germination [Figure 8B (5 min) for B. megaterium ; Figure 9B (30 min) for B. subtilis . The latter is apparent upon proper scaling and quantification of the gel image, data not shown] (Korza et al, 2016). …”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Since the work of Sinai et al, it is well recognized in the field that the general question of what, if any, cellular processes transpire during dormancy or germination needs further investigation. In the present issue, Korza et al (4) do exactly this by addressing the question of whether protein synthesis is required for germination in a different way than Sinai et al Korza et al inhibited protein synthesis during germination by depleting spores of rRNA. They found that rRNA depletion did not significantly reduce the rate of germination, strongly suggesting that protein synthesis is not required for germination.…”
mentioning
confidence: 85%